Pengembangan Wisata Religi Banten Lama - Riza Subban Alhakimi; Weishaguna (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. The issue which states that there are indications that Banten Lama religious tourism cannot develop from now on because stakeholders have not made efforts to develop religious tourism and have not paid more attention to its development. Then find out the problem. The problem covers two aspects, namely aspects of tourist attraction and aspects of management and service. Based on the above background, the formulation of the problem arises, whether religious tourism in Banten Lama can be more developed. With the aim of knowing whether or not the Old Banten religious tourism could be more developed. The analysis used in this research is descriptive analysis of the scale range. The analyzed aspect is the aspect of tourist attraction with the factors assessed are, tourist attraction, accessibility, tourism support facilities, tourism support services, conditions around the area and accommodation. Aspects of management and service with assessed factors are management and service, organizational structure, master plan, “Collaborative Management” of cross-sectoral agencies and Sapta Pesona. Answering from the problem formulation that says whether Banten Lama religious tourism can be more developed. Based on the results of the analysis and discussion in the previous chapter, it was concluded that the Old Banten religious tourism "Can Develop". For tourist attractions and management and services that are not yet developed, reviewing a development can be a must. The proposal is aimed at factors with criteria that are sufficiently developed and not developed, namely tourist attraction, conditions around the area, management and services, master plan and accommodation. Abstrak. Isu yang menyatakan bahwa ada indikasi wisata religi Banten Lama tidak dapat berkembang dari sekarang karena pemangku kepentingan belum berupaya dalam mengembangkan wisata religi serta kurang perhatian lebih terhadap pengembangannya. Kemudian diketahuilah permasalahannya. Permasalahannya mencakup kepada dua aspek, yaitu aspek daya tarik wisata dan aspek pengelolaan dan pelayanan. Berdasarkan latar belakang di atas, maka timbulah rumusan masalah, apakah wisata religi Banten Lama dapat lebih berkembang. Dengan tujuan, mengetahui wisata religi Banten Lama dapat tidaknya lebih berkembang. Analisis yang digunakan pada peneliatian ini adalah, analisis deskriptif rentang skala. Aspek yang dianalisis yaitu aspek daya tarik wisata dengan faktor yang dinilai adalah, daya tarik wisata, aksesibilitas, fasilitas pendukung wisata, layanan pendukung wisata, kondisi sekitar kawasan dan akomodasi. Aspek pengelolaan dan pelayanan dengan faktor yang dinilai adalah pengelolaan dan pelayanan, struktur organisasi, induk pengembangan (master plan), “Collaborative Management” instansi lintas sektor dan sapta pesona. Menjawab dari rumusan masalah yang mengatakan apakah wisata religi Banten Lama dapat lebih berkembang. Berdasarkan hasil analisis dan pembahasan pada bab sebelumnya diambil kesimpulan bahwasannya wisata religi Banten Lama “Dapat Berkembang”. Terhadap daya tarik wisata dan pengelolaan dan pelayanan yang belum berkembang, meninjau suatu pengembangan bisa menjadi keharusan. Usulan dituju pada faktor-faktor dengan kriteria cukup berkembang dan tidak berkembang yaitu daya tarik wisata, kondisi sekitar kawasan, pengelolaan dan pelayanan, induk pengembangan (master plan) dan akomodasi.